Development of VOCs gas sensor with high sensitivity using colorimetric polymer nanofiber: a unique sensing method. (20th September 2019) - Kim, Myoung Ok; Khan, Muhammad Qamar; Ullah, Azeem; Duy, Nam Phan; Zhu, Chunhong; Lee, Jung-Soon; Kim, Ick Soo
Abstract: A challenge for sensors detecting ultralow amount of volatile organic compounds (VOCs) in form of solvent or gas for reliable sampling and large surface area to volume ratio of sample must be studied. In this study, polydiacetylene (PDA)/ Polyurethane (PU) nanofibers web was manufactured using polydiacetylene, which was characterized by colorimetric. The manufactured nanofibers were exposed to volatile organic compounds (VOCs) solvents and gases to examine color changes and to monitor the reaction rate by manufacturing films under the same conditions. When PDA/PU nanofibers were exposed to VOCs solutions and vapors, color alteration was occurred from blue to red, which enabling the VOCs detection. In addition, the colorimetric response (CR) is high in the nonpolar and aprotic solvents, and lower in the lower the polarity of the solvent.. This colorimetric response (CR) is expected to enable qualitative analysis between solvents. Also, it was confirmed that nanofibers have higher sensitivity and faster reaction rate than films due to changes in color of nanofibers and films. The PDA/PU nanofibers developed through this study are expected to be available as colorimetric sensors for VOCs detection through rapid colorimetric response.